How does mobility and urban environment affect the migrants’ settlement intention? A perspective from the intergenerational differences - Liang, Xiaoxiang; Li, Qingyin; Zuo, Wen; Wu, Rong (Frontiers in Public Health, 2024)
With China embracing a new people-centered urbanization stage, the problem of migrants "flowing without moving" has become increasingly prominent, and settlement intention has gradually garnered attention. Therefore, based on questionnaire data from the China Labor Force Dynamic Survey 2016, this study uses a multilevel linear regression model to explore the influence of mobility, social environment, built environment, and demographics characteristics on settlement intention in the migrants and discusses differences between settlement intention of new and old generations and their internal influence mechanism. The findings are as follows: 1) Compared to the old generation, the new migrant generation generally has higher settlement intention 2) The migrants' settlement intention is influenced mainly by mobility, social environment, built environment and demographics characteristics; 3) For the new migrant generation, social and demographic characteristics significantly influence their settlement intention. 4) The floating and built environment of the old generation significantly influence their settlement intention. Finally, this paper argues that there are differences in the influence mechanism of the same factors on settlement intention of the new and old generations of the migrants and proposes differentiated policy suggestions for the migrants to promote their real integration into cities.